Towards the large-scale production and strength prediction of near-eutectic AlxCoCrFeNi2.1 alloys by additive manufacturing. (August 2020) - Joseph, J.; Imran, M.; Hodgson, P.D.; Barnett, M.R.; Fabijanic, D.M.
Highlights: Production of large homogeneous eutectic high entropy alloys using laser engineered net shaping. Eutectic high entropy alloy with lamellar structure exhibited excellent strength, work hardening and plasticity. Yield strength of the dual-phase alloys followed the rule-of-mixtures based on the yield strength and volume fraction of constituent phases. Abstract: This work demonstrates the potential of laser engineered net shaping (LENS) to fabricate near-eutectic Alx CoCrFeNi2.1 high-entropy alloys from elemental powders. The as-deposited alloys consisted of FCC and B2 phases and revealed a change in microstructure from dendritic to lamellar with an increase in Al-concentration. The strength of the Alx CoCrFeNi2.1 alloys can be expressed as a function of the volume fraction of the constituent phases. Our results suggest that LENS can be readily adapted to large-scale production of these alloys from elemental powders with excellent microstructural homogeneity, printability and mechanical properties, and avoids the use of expensive pre-alloyed powders.